Central exclusive production of J/ψ and ψ(2S) mesons in pp collisions at √ s =13 TeV; Journal of High Energy Physics; № 10 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen